A NEW TECHNIQUE OF HARVESTING AND ISOLATION OF PLANT PATHOGENIC FUSARIUM FROM FUSARIUM AFFECTED SOIL - S. G. BORKAR; A. R BHAGWAT; .S AJAYASREE (The Bioscan, 2019)
Isolation of plant pathogenic Fusarium spp. from soil samples of wilt infected crop soils is a tedious task due to appearance of several fungal, bacterial and actinomycetes spp, present in such soil sample, in the isolation plates. A new technique for harvesting and isolation of plant pathogenic fusarium directly from soil samples was developed. Out of different fruits and vegetables slices charged with the infected soil sample, the ripen tomato fruit slices was able to harvest the fusarium pathogen with its fungal growth and sporulation. The harvested fusarium, then was easy to grown on routinely used fungal medium. Isolation of Fusarium directly from the soil sample, on tomato disc is a new technique of harvesting of Fusarium from fusarium infected soil samples and can be used by plant disease diagnostic labs for assessment of presence of Fusarium wilt pathogen in the soil. This is a new and cheap technique of assessment of fusarium in the soil samples rather than using a costly specialised media for the isolation of fusarium directly from soil samples.